Methanol as a High Purity Hydrogen Source for Fuel Cells: A Brief Review of Catalysts and Rate Expressions - Madej-Lachowska Maria; Kulawska Maria; Słoczyński Jerzy (Chemical and Process Engineering)
Hydrogen is the fuel of the future, therefore many hydrogen production methods are developed. At present, fuel cells are of great interest due to their energy efficiency and environmental benefits. A brief review of effective formation methods of hydrogen was conducted. It seems that hydrogen from steam reforming of methanol process is the best fuel source to be applied in fuel cells. In this process Cu-based complex catalysts proved to be the best. In presented work kinetic equations from available literature and catalysts are reported. However, hydrogen produced even in the presence of the most selective catalysts in this process is not pure enough for fuel cells and should be purified from CO. Currently, catalysts for hydrogen production are not sufficiently active in oxidation of carbon monoxide. A simple and effective method to lower CO level and obtain clean H2 is the preferential oxidation of monoxide carbon (CO-PROX). Over new CO-PROX catalysts the level of carbon monoxide can be lowered to a sufficient level of 10 ppm.